Impact of Transforming Organizational Culture and Digital Transformation Governance toward Digital Maturity in Indonesian Banks - Hie, Bayu Prawira (International Review of Management and Marketing, 2019)
The purpose of this research was to know and analyze the effect of transforming organizational culture and digital transformation governance on digital maturity in banks in Indonesia. The population in this research was bankers in Indonesian banks with a sample size of 611 respondents. The method used in this research was descriptive and explanatory survey method, and the data analysis method used was structural equation modeling with data analysis tools Lisrel 8.80. The results showed that transforming organizational culture and digital transformation governance simultaneously have a positive and significant effect on digital maturity with a contribution of 61%. The digital transformation governance partially has more dominant influence on digital maturity compared to transforming organizational culture. The managerial implication of the results of this study was that to reach higher digital maturity in Indonesian banks, leaders must emphasize in digital transformation governance with removing silos as the main dimension to focus on. Keywords: Organizational Culture; Digital Transformation; Governance; Technology; Bank JEL Classifications: O32, M54, N75 DOI: https://doi.org/10.32479/irmm.8785